Syirkah Maza'arah Business Model for Economic Recovery: A Case Study of D'Durian Park: Model Bisnis Syirkah Maza'arah untuk Pemulihan Ekonomi: Studi Kasus Taman D'Durian - Fauji, Imam; Masruchin, Masruchin; Krisnaningsih, Diah; Aprilia, Yohana; Rahmansyah, Panji (Indonesian Journal of Law and Economics Review, 2023)
The COVID-19 pandemic's profound impact on the global economy and Indonesia's growth necessitates innovative solutions. This study investigates the efficacy of the syirkah maza'arah business model for fostering microeconomic growth and accelerating economic recovery. Through a qualitative case study approach, the research examines the implementation of the syirkah maza'arah theory in the context of D'Durian Park, an agribusiness in Jombang. The park operates under a cooperative system between landowners and managers, contributing to a balanced profit-sharing mechanism. The study offers insights into the applicability of this Islamic business concept in rejuvenating economies, particularly in times of crisis, and highlights its potential for wider adoption. Highlight: Global Economic Impact: This study addresses the far-reaching consequences of the COVID-19 pandemic on the global economy and Indonesia's growth, emphasizing the need for innovative solutions. Syirkah Maza'arah Model: Investigating the effectiveness of the syirkah maza'arah business model, the research delves into its potential to foster microeconomic growth and expedite economic recovery. Real-world Application: Through a qualitative case study of D'Durian Park, the study demonstrates how the syirkah maza'arah theory is applied in an agribusiness context, showcasing a cooperative profit-sharing system between landowners and managers. The research highlights the concept's relevance in revitalizing economies during crisis and suggests its broader adoption as a viable strategy. Keyword: COVID-19 Pandemic, Syirkah Maza'arah, Microeconomic Growth, Economic Recovery, Qualitative Case Study